Formulation process, physical stability and herbicidal activities of Cymbopogon nardus essential oil-based nanoemulsion - Naphat Somala; Chamroon Laosinwattana; Montinee Teerarak (My University, 2022)
Abstract Essential oil-based bioherbicides are a promising avenue for the development of eco-friendly pesticides. This study formulated nanoemulsions containing citronella ( Cymbopogon nardus ) essential oil (CEO) as an herbicidal product using a high-pressure homogenization method with hydrophilic-lipophilic balance (HLB) values ranging 9–14.9 for the surfactant mixture (Tween 60 and Span 60). The CEO was high in monoterpene compounds (36.333% geraniol, 17.881% trans -citral, 15.276% cis -citral, 8.991% citronellal, and 4.991% β -citronellol). The nanoemulsion at HLB 14 was selected as optimal due to having the smallest particle size (79 nm, PI 0.286), confirmed by transmission electron microscopy. After 28 days of storage, particle size in the selected formulation changed to 58 and 140 nm under 4 °C and 25 °C, respectively. Germination and seedling growth assays with Echinochloa crus-galli showed that the nanoemulsion exerted a significant dose-dependent inhibitory effect at all tested HLBs (9–14.9) and concentrations (100–800 µL/L). The inhibitory effect was greatest at HLB 14. Treatment of E. cruss-galli seed with the HLB 14 nanoemulsion significantly reduced seed imbibition and α -amylase activity. Our findings support that CEO nanoemulsions have a phytotoxic effect and hence herbicidal properties for controlling E. cruss-galli . Accordingly, this nanoemulsion may have potential as a bioherbicide resource.
Keywords: Allelopathy and phytotoxic interactions